Moringa oleifera leaf flour biscuits increase the index of erythrocytes in pregnant women with anemia - Monika Loa; Healthy Hidayanty; Sharvianty Arifuddin; Mardiana Ahmad; Veni Hadju (Elsevier, 2021)
Background: Moringa Oleifera leaves contain nutrients such as proteins, iron, and vitamin C that potentially prevent anemia more common in pregnant women. In the manufacture of cookies that are substituted Moringa Oleifera leaf flour substitution, 40% obtained Fe levels 22.68 ppm so that it can be developed to prevent anemia. The purpose of this research is to know the effect of giving biscuits (cookies) Moringa Oleifera leaf flour to index erythrocytes (MCH, MCHC, MCV) of pregnant women with anemia. Method: It was a quasi-experiment research with design nonequivalent Control Group design. The research was conducted at Antang, Mamajang, and Batua Public Health Center in Makassar, examination of hematology analyzer in the Clinic Pathology Laboratory of Universitas Hasanuddin Hospital. Sampling techniques using purposive sampling. Samples were pregnant women with trimester I and III anemia amounted to 25 samples on the biscuit moringa group and 25 samples in the control group. Data were analyzed using test Paired T-Test, T-Test Independent, Wilcoxon, and Mann - U Withney. Result: Characteristics of age, gestational age, income, physical activity, education, and parity of both groups has been comparable before the treatment with the value p > 0.05, with most of the samples aged 20-35 years having a pregnancy age of 4-8 weeks, income IDR 1 million - IDR. 2 million, activity score Baecke 6.00-7.25, Senior High School education, parity >1. A significant average increase in the value of MCH from 27.55 to 28.00 and MCV from 78.57 to 78.93 in the group provided biscuits (cookies) of Moringa Oleifera leaf flour with p-value <0.05, in the control group, occurred an average but insignificant increase with p-value >0.05. The MCHC Group control and biscuit moringa group had an average increase, but both were not statistically significant, p > 0.05. There is a significant difference in increased MCH and MCV erythrocyte indices between the biscuit moringa and control groups with a p-value <0.05. As for the MCHC value, the two groups do not differ meaningfully with p-value = 0.611, p > 0.005. Conclusion: There is the effect of giving biscuits (cookies) Moringa Oleifera leaf Flour Against the index of erythrocytes MCH and MCV in pregnant women with anemia. However, it has no effect on the MCHC value of pregnant women with anemia. It is recommended for pregnant women to utilize local plants, the Moringa Oleifera leaves to fulfill the intake of nutrients that can help pregnant women from anemia.